PRINSIP TAUHID SEBAGAI LANDASAN INTEGRASI ILMU AGAMA DAN SAINS DALAM KURIKULUM - Nuril Khoiriyah; Fatimah Aulia Izzah Billah; Dewi Putri Suci; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
Islamic educational philosophy plays a strategic role in developing a monotheism-based educational paradigm. This paradigm seeks to make the values ​​of faith in Allah the primary foundation for all aspects of education, including curriculum, methods, and ultimate goals. This article examines the concept of monotheism as the core of Islamic educational philosophy and its relevance in addressing the challenges of modern education. This research employed qualitative methods with a descriptive-analytical approach. The results demonstrate that monotheism-based education can shape complete human beings capable of harmonizing spiritual, intellectual, and moral aspects. Therefore, implementing a monotheism-based educational paradigm is essential for developing a generation with character and responsibility, both individually and socially. In addition, tauhid-based education provides a solution to overcome the dualism of education by harmonizing religious and secular knowledge. This approach helps students maintain their Islamic identity while remaining open to the development of science and technology that is in accordance with Islamic values. Therefore, the philosophy of Islamic education based on tauhid not only offers a strong conceptual foundation but also has practical relevance in developing an educational system that guides students toward success and well-being in both worldly life and the hereafter.